當代科學與迷信之哲學反思: Philosophical Reflections on Contemporary Sciences and Superstitions - LIU, Dachun (International Journal of Chinese & Comparative Philosophy of Medicine, 2001)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 可檢驗性是區分科學與偽科學的一個關鍵。它至少包含三層意思：第一，它意味着科學實驗是最基本的科學實踐活動，實驗方法是科學的標誌。第二，它為科學假說提供了一個基本的方法論原理，不論是提出假說還是鑒別假說。第三，它是科學發現獲得社會承認的基本條件。如果一個假說在原則上是不可檢驗的，那它就不能稱為科學。偽科學乃是打着科學旗號、冒充科學的虛假的東西，我們需要仔細分辨，予以揭露。同時，我們也需要認識到，在現代社會的複雜系統中，雖然科學起着主導作用，但科學不是全體，是不是一切。有許多非科學的東西，如宗教、藝術、習俗等，對於社會發展是十分重要的，不能一概否定。但它們也不必硬說成是科學。 There is an important way to distinguish science from pseudo-science：empirical testability. It has three basic implications. First, scientific experiments are the fundamental scientific activities, and the method of experiment marks empirical science. Second, empirical testability constitutes the first methodological principle for proposing or affirming a scientific hypothesis. Finally, it is also a basic condition for a scientific discovery to be accepted by society. If a hypothesis cannot be tested even in principle, it cannot be termed as a scientific hypothesis. In contemporary Chinese society, there are varieties of pseudo-sciences. They use the name of science to identify themselves, but cannot pass the serious requirement of empirical testability. We should carefully examine such pseudo-sciences and disclose the nature of their hypotheses and activities as non- or anti-science. At the same time, we should also recognize that, although science is dominant in contemporary society, it is not everything valuable. There are a great deal of other items, such as religion, art, and customs, which are nonscientific but are extremely important to the development of society. We should not deny the value of non-scientific theories or activities. Neither should we mark them as science. DOWNLOAD HISTORY | This article has been downloaded 28 times in Digital Commons before migrating into this platform.